UM ESPAÇO DE BRINCAR:O cotidiano numa brinquedoteca hospitalar - Lopes, Bruna Alves (2014)
This study aims to analyze the role of hospital toy library and daily that space in a hospital specializing in pediatric care administered by the City Hall of Ponta Grossa/PR. To achieve our goal we present, at first, the process of construction of the hospital as a place of healing, and then visualize the paths that allowed discussions on the inclusion of play and toy libraries in the hospital. We start from the understanding that tensions and conflicts are part of social relations as a whole, being pronounced in spaces permeated by power relations. Introducing the hospital as an environment marked by tensions, conflicts and power relations and the toy library as a possibility – through free play – subvert the powers that be in these spaces, while they are also marked by disputes, conflicts and tensions. We adopt the theoretical category daily by their importance for understanding the processes of change and disruption that occur in society. From Foucault (1987) and Certeau (1994), we understand the daily as the space in which the micro powers are at the same time, exercised and circumvented by the subjects. The research is qualitative and the methodology adopted is the Case Study understood by Gil (2009) as a research design, and relevant to recent phenomena. We perform the triangulation of techniques and sources, being they the field observations, interviews and document analysis. In this work we adopt an interdisciplinary perspective – as this concept is presented by Muñoz and Oliveira Junior (2009) – understood as a dialogue between different disciplines in order to build both theoretical and methodological paths, and the drafting of new problems. We observed that the toy library of the institution was built on the principles of humanization of health care for the child, and their services are grounded in free play. In this sense such spaces collaborate in developing bonds of friendship, the bond between children and mothers through play, besides being one of the few places within the hospital in which the child has the power to choose, and to say no to any activity that not like. In contrast, we found that the main problems for the maintenance of services is the lack of professionals in sufficient numbers to work in these areas, limiting the opening time of the toy library (one hour per day), acquiring and retaining the playful collection (acquired solely through donations), and cleaning the space that often does not occur due to lack of professionals in the institution.